2020
DOI: 10.1111/apa.15551
|View full text |Cite
|
Sign up to set email alerts
|

Prescribing in a paediatric emergency: A PERUKI survey of prescribing and resuscitation aids

Abstract: Aim The aim was to investigate the use of paper‐based and electronic prescribing and resuscitation aids in paediatric emergency care from a departmental and individual physician perspective. Methods A two‐stage web‐based self‐report questionnaire was performed. In stage (i), a lead investigator at PERUKI sites completed a department‐level survey; in stage (ii), individual physicians recorded their personal practice. Results The site survey was completed by 46/54 (85%) of PERUKI sites. 198 physicians completed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…The app was used from January 2016 to December 2019 for 59,375 children whose median age was 1 year (IQR 0-3 years). The app was used for 33,874 (57.05%) infants, 16 Table 2 shows the clinical characteristics of the patients for whom the app was used. Among the 62,542 chief complaints selected, 49,101 (78.51%) were "sickness" and 13,441 (21.49%) were "injury, poisoning, foreign substances and others."…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The app was used from January 2016 to December 2019 for 59,375 children whose median age was 1 year (IQR 0-3 years). The app was used for 33,874 (57.05%) infants, 16 Table 2 shows the clinical characteristics of the patients for whom the app was used. Among the 62,542 chief complaints selected, 49,101 (78.51%) were "sickness" and 13,441 (21.49%) were "injury, poisoning, foreign substances and others."…”
Section: Resultsmentioning
confidence: 99%
“…Many mobile apps for medical personnel have been developed in the field of pediatric emergency medicine. For instance, another study on medical app use in Irish pediatric emergency departments reported that one-third of medical facilities and about half of the medical personnel had medical apps installed on their personal mobile devices, with the most adopted app being the British National Formulary app developed by the NHS [ 16 ]. However, the effectiveness of medical apps used by the general public has not been well evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Peer‐reviewed articles have documented the use of apps in veterinary medicine in small animals, 18 horses, 19 food animals, 20 and exotic animals 21 . Furthermore, smart phone apps are ubiquitous in human medical disciplines, such as burn management, 22 dermatology, 23 pediatrics, 24 emergency medicine, 25 and surgery 26 …”
Section: Discussionmentioning
confidence: 99%
“…In the United Kingdom, where this study was conducted, the National Institute for Health Research (NIHR) deem health care professional research of this kind as not requiring formal ethical review (hra-decisiontools.org.uk). evaluative questionnaires run for Pediatric Acute Care topics of investigation (12,13).…”
Section: Methodsmentioning
confidence: 99%